Current pharmacogenetic developments in oral anticoagulation therapy: The influence of variant VKORC1 and CYP2C9 alleles - Oldenburg, Johannes; Bevans, Carville G.; Fregin, Andreas; Geisen, Christof; Müller-Reible, Clemens; Watzka, Matthias (Thrombosis and Haemostasis, 2007)
For decades coumarins have been the most commonly prescribed drugs for therapy and prophylaxis of thromboembolic conditions. Despite the limitation of their narrow therapeutic dosage window, the broad variation of intra- and inter-individual drug requirement, and the relatively high incidence of bleeding complications,prescriptions for coumarins are increasing due to the aging populations in industrialised countries.The identification of the molecular target of coumarins,VKORC1, has greatly improved the understanding of coumarin treatment and illuminated new perspectives for a safer and more individualized oral anticoagulation therapy. Mutations and SNPs within the translated and non-translated regions of the VKORC1 gene have been shown to cause coumarin resistance and sensitivity,respectively. Besides the known CYP2C9 variants that affect coumarin metabolism, the haplotype VKORC1*2 representing a frequent SNP within the VKORC1 promoter has been identified as a major determinant of coumarin sensitivity,reducingVKORC1 enzyme activity to 50% of wild type. Homozygous carriers of the VKORC1*2 allele are strongly predisposed to coumarin sensitivity. Using individualized dose adaptation, a significant reduction of bleeding complications can be expected, especially in the initial drug saturation phase. Furthermore, concomitant application of low dose vitamin K may significantly reduce intra-individual coumarin dose variation and, thus, may stabilize oral anticoagulation therapy. The use of new pharmacogenetics-based dosing schemes and the concomitant application of low-dose vitamin K with coumarins will decidedly influence the current practice of oral anticoagulation and greatly improve coumarin drug safety.
Keywords: VKORC1; CYP2C9; acenocoumarol; phenprocoumon; warfarin; genotype